Chirp‐Style GNSS Jamming Signal Tracking and Geolocation. Issue 1 (March 2016) - Mitch, Ryan; Psiaki, Mark; Ertan, Tunc
Abstract: Algorithms for tracking and geolocating the chirp‐style signals emitted by Global Navigation Satellite System (GNSS) jammers are presented. Jammer use is a growing problem that can be mitigated by locating the devices, confiscating them, and sanctioning their users. Therefore, a Kalman filter that uses a chirp‐style signal model and an FFT‐based measurement model are developed for tracking GNSS jammer signals. The tracking results become inputs to a time‐of‐arrival geolocation Kalman filter. The algorithms are verified using real jammer data. Copyright © 2016 Institute of Navigation